Global research trends on platelet-rich plasma for tendon and ligament injuries from the past two decades: A bibliometric and visualized study - Xu, Jie; Du, Wanli; Xue, Xiali; Chen, Meng; Zhou, Wenqi; Luo, Xiaobing (Frontiers in Surgery, 2023)
Background: In sports medicine, tendon and ligament injuries are the most prevalent conditions, and with the booming of sports competition, the incidence of sports injuries is gradually increasing, investigating more potent therapeutic options is therefore becoming increasingly crucial. Platelet-rich plasma therapy has gained popularity as an effective and secure treatment in recent years. Currently, a faceted systematic and clear visual analysis is lacking in this research area. Methods: The literature related to using platelet-rich plasma to treat ligament and tendon injuries from 2003-2022 in the core dataset of the Web of Science database was collected and analyzed visually using Citespace 6.1 software. Research hotspots and development trends were analyzed in terms of high-impact countries or regions, authors, research institutions, keywords, and cited literature. Results: The literature comprised a total of 1827 articles. The annual publication volume of relevant literature has demonstrated a significant development tendency as the field of platelet-rich plasma research for tendon and ligament injuries has heated up in recent years. With 678 papers, the United States came in top place, followed by China with 187 papers. Hosp Special Surg ranked first with 56 papers. Maffulli N, University of Salerno, Italy, ranked first with 48 publications. AMERICAN JOURNAL OF SPORTS MEDICINE has both the largest output and the most citations. Conclusion: Analysis of the research literature over the past 20 years shows that the United States and China will continue to dominate in terms of volume of publications based on annual volume and trends, with some collaboration among high-impact authors.The applicability of PRP in many diseases remains controversial, and the precise cellular transduction pathways through which platelet-rich plasma affects tendon ligament healing still needs to be more clearly established because there aren't enough thorough basic molecular biology studies, particularly in vitro experiments and animal models. The hot research topics analyzed by keywords were tennis elbow, anterior cruciate ligament, rotator cuff repair, achilles tendon, mesenchymal stem cells, guided tissue regeneration, network meta analysis, chronic patellar tendinopathy, and follow up, and the research trends were hyaluronic acid, clinical outcomes, rotator cuff tears, mesenchymal stem cells, growth factors, and follow up.